Dylematy oceny jakościowej projektów społecznych: Dilemmas of qualitative evaluation of social projects - Szot-Gabryś, Teresa (Management and Administration Journal, 2021)
A characteristic feature of social projects is that they produce ''soft'' outcomes. Changes that ought to result from execution of a given project are usually qualitative in nature. Thus, it is highly difficult to judge whether the forecast project outcomes commensurate with the funds provided for its implementation in the budget. The above issues are illustrated in the article with the use of a case study involving a social transborder project.